Performance of bean seeds from plants submitted to water deficit in two growing stages - Pasin, Névio Henrique; Filho, Benedito Gomes dos Santos; Santos, Dora Suely Barbosa dos; Mello, Vera Delfina C. (Pesquisa Agropecuaria Brasileira, 1991)
This work was carried out in greenhouse to study the water deficit effect during the pre-flowering and pod fulfillment periods, on the physiological quality and chemical composition of bean (Phaseolus vulgaris L.) seeds, cultivars Rio Tibagi, Rio Negro and EMPASC 201-Chapecó. The water deficit was imposed through interruption of irrigation during eight days. The physiological quality of seeds was evaluated by germination percentage, vigor in first count, speed of emergence, initial population, height of the seedlings and roots and acid phosphatase activity. The chemical composition was evaluated through starch concentration, soluble sugars, amino acids, and soluble proteins. Water deficit during the pre-flowering did not affect the physiological quality of the seeds, but during pod fulfillment it reduced the vigor expressed in the emergence, speed initial population and acid phosphatase activity. Plants stressed during the pod fulfillment produced seeds with less starch and more soluble sugars rate, with no changes on amino acids and soluble protein concentration.
Keywords: cultivars; Phaseolus vulgaris; physiological seed quality